(3GdYHGOdIs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3gPG cJGH PcQfG ajg eG fWbJ Hg GdSfI GdYHGOdjI heG JQLeJg dbdhH GdYGQajf GdebQHjf Yf GdSfI GdbghGfjg s
(3BNQgG (B:s
(3hgh GdeTHg HGddHf hYde GdQShe hgh Ydj s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdNGeSIs
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B257s
Keywords: (3GdJUha hGdBOGH GdTQYjIs